The molecular basis of selective permeability of connexins is complex and includes both size and charge - Nicholson,B.J. (2000)
Although gap junction channels are still widely viewed as large, non-specific pores connecting cells, the diversity in the connexin family has led more attention to be focused on their permeability characteristics. We summarize here the current status of these investigations, both published and on-going, that reveal both charge and size selectivity between gap junction channels composed of different connexins. In particular, this review will focus on quantitative approaches that monitor the expression level of the connexins, so that it is clear that differences that are seen can be attributed to channel properties. The degree of selectivity that is observed is modest compared to other channels, but is likely to be significant for biological molecules that are labile within the cell. Of particular relevance to the in vivo function of gap junctions, recent studies are summarized that demonstrate that the connexin phenotype can control the nature of the endogenous traffic between cells, with consequent effects on biological effects of gap junctions such as tumor suppression.